A chiral fermionic valve driven by quantum geometry - Anvesh Dixit; Pranava K. Sivakumar; Kaustuv Manna; Claudia Felser; Stuart S. P. Parkin (Nature, 2026)
Abstract Multifold topological semimetals host fermions with opposite chiralities at topological band crossings 1–3 . Chiral fermionic transport in topological systems often relies on high magnetic fields or magnetic dopants to suppress trivial transport and create an imbalance in occupancy of opposite Chern-number states 4,5 . Here we use the quantum geometry 6,7 of topological bands to filter fermions by chirality into distinct Chern-number-polarized states. This allows for the real-space separation of currents with opposite fermionic chiralities, which we have demonstrated by observing their quantum interference in the absence of any magnetic field. Devices fabricated from single-crystal PdGa in a three-arm geometry exhibit quantum-geometry-induced anomalous velocities 8,9 of chiral fermions, thereby exhibiting a nonlinear Hall effect. The resultant transverse chiral currents with opposite anomalous velocities are thereby spatially separated into the outer arms of the device. These chiral currents in opposing Chern number states also carry orbital magnetizations with opposite signs. The mesoscopic phase coherence of these chiral currents facilitated their quantum interference 10 in a Mach–Zehnder interferometer. Our findings establish a chiral fermionic valve that exhibits three key properties: spatially separates chiral fermions into Chern-number polarized states by using their quantum geometry, enables tuneable current-induced magnetization and provides a platform for controllable quantum interference of chiral quasiparticles using an electric current and magnetic field.